Ver para ler? Tradução e multimodalidade em tarefas de leitura de livros didáticos de língua inglesa do PNLD 2017 - Lima, Ana Maria Barreto de (2020)
As a result of the technological advances experienced in the contemporaneity, the multimodal resources are more and more involved in interactions, influencing the ways of saying, translating and reading. Consequently, it is vital to investigate how translation as a pedagogical tool and multimodality are approached and integrated in the English textbooks approved by Programa Nacional do Livro e do Material Didático- PNLD-2017 and what are their effects on the students’ reading comprehension. This quali-quantitative descriptive research had as methodological procedures the analysis of the reading comprehension activities from the textbooks Team Up and Way to English for Brazilian learners and the application of some activities from these textbooks with students from two municipal schools of Fortaleza. First, we investigated how the translation and multimodality were approached and integrated in the reading sections of the referred materials. Second, we examined the students’ performance when reading texts with and without images in translation and comprehension activities and the strategies used by them. The theoretical foundations for this study are based on the works of Branco (2011), Lucindo (2006) and Tessaro (2012) who advocated for translation as a pedagogical tool. To analyze the multimodal aspect, we based this study on the Grammar of Visual Design by Kress and van Leeuwen (2006), as well as on Liu’s (2013) meta-interpretive strategies and the analysis of Carvalho (2016). We also took into consideration the multileteracy’s studies such as Rojo’s study (2012). The results revealed that the translation is approached in the materials as a mechanical, uncritical and purposeless practice that does not lead to an active and critical reading process in the reading sections activities. The results also revealed that the intersemiotic translation is the most addressed type of translation, which facilitates the dialogue with the multimodality in these activities. Nevertheless, the integration between translation and multimodality is still incipient, even though the results showed that the images helped the students during the reading activity.